Hijos de la fábula de Fernando Aramburu: un intento de erradicar la dialéctica del "conflicto vasco" (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2024)
Hijos de la fábula (2023) shows us the myths that support the doctrine of terrorism by two young people, Asier and Joseba, natives of Guipúzcoa. Throughout its pages, Fernando Aramburu captures the ideological crucible that drives the thoughts of the ETA terrorist, using satire to do so. The writer manages to arouse in the reader a myriad of feelings, from confusion to laughter to sadness, encompassing deep respect for those who suffered the evil of violence. The novel is revealed as an instrument of delegitimization of myths that last, and continue, to this day.
Keywords: terrorism; ETA; fable; violence; chimera; GDG; myths; victims; restorative stories.